The Descriptions and Attitudes of Riders and Arena Owners to 656 Equestrian Sport Surfaces in Sweden - Egenvall, Agneta; Roepstorff, Lars; Peterson, Michael; Lundholm, Marcus; Hernlund, Elin (Frontiers in Veterinary Science, 2021)
Horses in equestrian sports are commonly trained in arenas with prepared footing. Information on the number and variants of such arenas is generally unknown. This paper provides an overview of the primary construction types of riding surfaces in Sweden including details on composition, constructions principles, usage frequency, maintenance and cost of operation as well as to investigate rider perception of the ideal arena properties using a large population of riders. Data on 656 equestrian surfaces in Sweden obtained up to 2014 are presented, of which 373 were outdoor and 283 indoor were arenas. Dressage and show-jumping were the main disciplines conducted in the arenas. Sand-mineral arenas were most common outdoors and sand-woodchips arenas most common indoors, followed by sand-fibre arenas and even fewer synthetic arenas. Comparing the three most common arena types, dragging was most often done on sand-woodchips and sand-fibre arenas. Harrowing was less often done on sand-mineral arenas compared to sand-woodchips and sand-fibre arenas. Combining dragging, harrowing, deep harrowing and rolling arenas with higher usage were maintained more frequently, compared to those used less frequently. It was commonly claimed that the top-layer needs renovation every other-4th year or every 5th to 10th year. Few respondents allocated more than 10,000 SEK in yearly maintenance costs, with the exception for sand-woodchips and sand-fibre arenas followed by synthetic arenas. The shortest duration perceived between required renovations was found for sand-woodchips top-layer arenas. Ideal surface properties were evaluated by 3158 riders. Dressage and show-jumping riders differed somewhat regarding ideal spans of functional arena properties: for impact firmness, responsiveness and grip. The current study likely included well utilised arenas, compared to those less well utilised. The resources necessary to keep an arena consistent over time seemed underestimated. Knowledge of maintenance and priorities for arenas are important to users and arenas managers, be they construction companies or arena managers in order to maximise the outcome of efforts for arena improvement and optimise locomotor health for horses that use them. Further, many arenas were new and research into organic arena management is important, especially if equestrians continue to build and renew arena surfaces.